A Detailed State of the Art Review on Membrane Based Heat Exchanger Technologies for High Pressure Syngas Management in Underground Coal Gasification - Sagar S. Gaddamwar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Underground Coal Gasification (UCG) represents a promising pathway for utilizing deep and unmineable coal reserves while minimizing surface environmental impacts. One of the most critical engineering challenges in UCG systems is the effective handling and cooling of synthesis gas generated at elevated temperatures and pressures within underground coal seams. Inefficient thermal management of syngas can lead to severe operational risks, including excessive thermal stresses, material degradation, and pressurerelated failures. In recent years, membrane-based heat exchanger configurations have emerged as viable solutions for enhancing heat transfer performance under extreme operating conditions. This review paper presents a comprehensive and detailed assessment of membrane based heat exchangers particularly membrane helical coil and membrane serpentine tube configurationsused for highpressure syngas cooling in underground coal gasification systems. The paper systematically analyzes syngas properties, heat transfer mechanisms, computational and experimental studies reported in the literature, comparative performance trends, and existing design limitations. Key research gaps are identified, and future research directions are proposed to guide the development of reliable and efficient thermal management systems for underground coal gasification applications.